Brainstem Auditory Evoked Responses in an Equine Patient Population. Part II: Foals. (5th June 2014) - Aleman, M.; Madigan, J.E.; Williams, D.C.; Holliday, T.A.
<x xml:space="preserve">Abstract</x> Background Reports of the use of brainstem auditory evoked response (BAER) as a diagnostic modality in foals have been limited. Hypothesis/Objectives To describe BAER findings and associated causes of hearing loss in foals. Animals Study group 18 foals (15 neonatal, 3 nonneonatal), control group (5 neonatal foals). Methods Retrospective. BAER records from the Clinical Neurophysiology Laboratory were reviewed from the years of 1982 to 2013. Peak latencies, amplitudes, and interpeak intervals were measured when visible. Clinical data were extracted from the medical records. Foals were grouped under disease categories. Descriptive statistics were performed. Results Ten neonatal foals had complete absence of BAER bilaterally and 5 had findings within reference range. Abnormalities were associated with common neonatal disorders such as sepsis, neonatal encephalopathy, neonatal isoerythrolysis, and prematurity. BAER loss also was observed in foals with specific coat color patterns such as completely or mostly white with blue irides or lavender with pale yellow irides. An American Miniature foal with marked facial deformation also lacked BAER bilaterally. One nonneonatal foal with an intracranial abscess had no detectable BAER peaks bilaterally, and 2 older foals, 1 with presumed equine protozoal myeloencephalitis and the other with progressive scoliosis and ataxia, had BAER within normal limits. Conclusions and Clinical Importance In neonatal foals, BAER deficits commonly are complete and bilateral, and associated with common neonatal disorders and certain coat and eye color patterns. Sepsis, hypoxia, bilirubin toxicity, and prematurity should be investigated as potential causes of auditory loss in neonatal foals.